(untitled) (Indian Journal of Public Health Research & Development, 2020)
Hyperchloremia is elevation of serum cholesterol level above normal (> 200 mg/dl). There are an association between cardiovascular diseases and high level of blood cholesterol. There are many risk factors of hypercholesterolemia as genetic, environmental, systematic disease as diabetes mellites and some drugs factors. A cross sectional study was conducted on adults who were attending Samara general hospital outpatients clinicduring the period from 5th February-30th April 2017. The information regarding the problem and demographic characterestics of persons was obtained according to a questionnaire and the weight, height, blood pressure, total blood cholesterol level was recorded. The results shows that the frequency of hypercholesterolemia among sample study was (54%).There is no significant association between frequency of hypercholesterolemia according to gender, age group, body mass index, family history and smoking habit but it has been reported that a significant association between high serum cholesterol and presence of hypertension, cardiac diseases and diabetes mellites